2005
DOI: 10.1089/cbr.2005.20.231
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Biodistribution Between 99mTc-Depreotide, 111In-DTPA-Octreotide, and 177Lu-DOTA-Tyr3-Octreotate in a Small Cell Lung Cancer Animal Model

Abstract: The low tumor-to-lung and tumor-to-liver activity concentration ratios for (99m)Tc-depreotide could result in a lower detection rate of SCLC with this compound versus (111)In-DTPA-octreotide. (177)Lu-DOTA-Tyr(3)-octreotate gave the highest tumor-activity concentration, and has, thus, the best properties for therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 13 publications
1
20
1
1
Order By: Relevance
“…The tumor/normal-tissue activity concentration ratio was highest for blood (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), and muscle vs. all other tissues (Table II). The lowest tumor/normal-tissue value was Table I.…”
Section: Biodistribution Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumor/normal-tissue activity concentration ratio was highest for blood (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), and muscle vs. all other tissues (Table II). The lowest tumor/normal-tissue value was Table I.…”
Section: Biodistribution Ofmentioning
confidence: 99%
“…Numerous studies on radiolabeled octreotide, or octreotate, have been made on nude mice xenografted with GOT1 (14)(15)(16)(17) or NCI-H69 (18)(19)(20)(21). Studies using radioiodinated meta-iodobenzylguanidine (MIBG) have been performed in vitro or on nude mice xenografted with BON tumors (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…The affinity and internalization of a radiolabelled SS analogue depend on the entire molecule, including chelating agent and radionuclide. Animal studies demonstrated higher SSTR affinity of DOTATATE versus DOTATOC, resulting in higher tumour/normal tissue (T/NT) ratios and better therapeutic effects [24,50,51]. 177 Lu-DOTATATE had a higher tumour uptake in CA20948-bearing rats than 88 Y- and 111 In-labelled analogues [24].…”
Section: General Methods Including Individualizationmentioning
confidence: 99%
“…Therapy has been suggested/performed in animals and patients using SS analogues labelled with various radionuclides, e.g. the Auger and conversion electron emitters 111 In and 103m Rh (low electron energy) [46,72], the β-emitters 177 Lu, 153 Sm, and 161 Tb (medium electron energy) [23,24,26,42,44,51,73,74,75] and 90 Y, and 188 Re (high electron energy) [76,77,78] and the α-particle emitters 225 Ac, 211 At and 213 Bi [66,67,68,79]. For radionuclides with a higher electron energy and thus longer range, the absorbed fraction/dose in small tumours will be lower than in larger tumours and tissue surrounding the tumours will be more highly exposed.…”
Section: General Methods Including Individualizationmentioning
confidence: 99%
“…99m Tc]depreotide, 19,20 have been successfully developed and used in the clinic for somatostatin receptor imaging. In addition, several radiolabeled peptides, such as [ Tclabeled bombesin analogues for tumor imaging, 22 and [ 64 Cu]RGD for a V b 3 integrin imaging, 23 have shown promising results.…”
Section: Introductionmentioning
confidence: 99%